PENINGKATAN KETERAMPILAN MENULIS LAPORAN DENGAN METODE PENEMUAN TERBIMBING SISWA KELAS IV-A MI TANADA SIDOARJO - Fitriyah, Nur Hida Yatul (Journal Of Islamic Elementary School (JIES), 2019)
This study aims to determine the application of guided discovery methods and improving report writing skills of class IV-A students of MI TANADA Sidoarjo after the guided discovery method is applied to my sub-themes and my ideals. This research is a classroom action research using the Kurt Lewin model. Data collection used in this study includes interviews, observation, non-tests and documentation. The results of the study show: 1) The application of guided discovery methods can be seen from the activities of teachers and students. Teacher activity in cycle I 73, then increases in cycle II to 86.3. Activities of students in cycle I 75, then increased in cycle II to 85.4. Then it can be concluded that the application of the guided discovery method to my sub-theme and my ideals is classified as good, 2) Increasing report writing skills after using the guided discovery method can be seen based on the class average value and the percentage of students’ mastery learning. The average value of the first cycle class reached 72.2 then increased in the second cycle to 81.7. The percentage of students’ mastery learning in the first cycle reached 72.5% then increased in the second cycle to 87.5%. Then it can be concluded that the application of guided discovery methods to my sub-themes and my ideals can improve report writing skills of class IV-A students of MI TANADA Sidoarjo.